2022
DOI: 10.1371/journal.pone.0268800
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and causes of pediatric uncorrected refractive error: Pooled data from population studies for Global Burden of Disease (GBD) sub-regions

Abstract: Background There are limited systematic reviews on the prevalence of uncorrected refractive errors in children. We aimed to summarize the prevalence and causes of pediatric uncorrected refractive error (URE) from studies in the Global Burden of Disease (GBD) sub-regions. Methods The pooled analysis used the individual participant data (ages less than 20 years old) from population-based studies around the world by regions. URE was defined as presenting VA < 6/18 and improving to ≥ 6/18 or ≥1 line on using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Uncorrected refractive error when the presenting visual acuity was less than 6/18, but improved to 6/18 or better with pinhole vision 31 .…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Uncorrected refractive error when the presenting visual acuity was less than 6/18, but improved to 6/18 or better with pinhole vision 31 .…”
Section: Methodsmentioning
confidence: 92%
“…Monocular moderate VI was defined as PVA < 6/18 to ≤ 6/60 in one eye and 6/6 to ≤ 6/18 in the other eye 31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review found that the age and region-standardised prevalence of uncorrected pediatric RE were 5.85 for every 1000 US children, 4.40 for every 1000 in the Eastern Mediterranean region, 3.41 for every 1000 in the Western Pacific region, and 2.26 for every 1000 in the Southeast Asian region. 17 While it has been suggested that environmental factors are responsible for these differences, it is likely that genetic and ethnic factors are more important. 6 …”
Section: Discussionmentioning
confidence: 99%
“…1 Globally growing rates of URE, especially in the paediatric population, necessitate a scalable vision screening strategy for diagnosis and timely management. 2 Early screening for RE is important as a child may not be able to express poor vision or a unilateral vision loss can be missed. Uncorrected or inaccurately corrected RE can lead to undesirable consequences, such as subnormal vision, amblyopia, asthenopia, binocular vision anomalies, and poor academic performance affecting the quality of life.…”
Section: Introductionmentioning
confidence: 99%